Estimating perceived parental substance use disorder: Using register data to adjust for non-participation in survey research. (August 2021) - Frederiksen, Kirsten Søndergaard; Hesse, Morten; Grittner, Ulrike; Pedersen, Mads Uffe
Highlights: Examined magnitude of parental substance use disorder (PSUD) in general population. Young people whose parents had PSUD were less likely to complete the survey. Adjusted the estimation of self-reported PSUD for non-participation through the use of register data. Survey-based self-reports likely underestimate number of youth experiencing PSUD. Abstract: Aims: To estimate the prevalence of parental substance use disorder (PSUD) in the general population based on young adults' reports adjusted for non-participation using register-based indicators of PSUD. Design: A national sample survey study combined with a retrospective register-based study. Setting Denmark. Participants 10, 414 young people (aged 15–25 years) invited to two national sample surveys in 2014 and 2015 (5, 755 participants and 4, 659 non-participants). Measurements: A crude prevalence of PSUD was calculated based on participants' reports. Parental data from medical, mortality, prescription, and treatment registers (from the young adults' birth until the time of the surveys) were used to estimate a register-based prevalence of PSUD for both participants and non-participants. Differences between participants and non-participants were analysed using bivariate comparisons. Inverse probability weighting was used to adjust for bias due to non-participation. The crude prevalence of PSUD based on survey data was adjusted using the ratio of incidence proportion of the register-based PSUD compared with the survey-based PSUD. Findings: A total of 731 (12.7%) of the 5, 755 survey participants reported PSUD. Register-based PSUD was more common among non-participants (856/4, 659; 18.4%) compared with participants (738/5, 755; 12.8%, OR = 1.53, 95% CI 1.38–1.70). The adjusted estimate of the survey-based PSUD increased by 2.5 percentage points, from 12.7% to 15.2%. Conclusions: In the absence of register data, youth-reported PSUD is likely to underestimate the number of young people experiencing PSUD.